2003
DOI: 10.1074/jbc.m206730200
|View full text |Cite
|
Sign up to set email alerts
|

Anomeric Specificity of the Stimulatory Effect ofd-Glucose on d-Fructose Phosphorylation by Human Liver Glucokinase

Abstract: (2) analyzed the cooperativity of human B-cell glucokinase through such a stimulatory effect of D-glucose on D-fructose phosphorylation. They concluded that the effect of the aldohexose on D-fructose phosphorylation indeed reflects the positive cooperativity for D-glucose, as mediated by its binding to the catalytic site. Further experiments conducted in isolated rat pancreatic islets have documented that D-glucose also causes a concentration-related increase in the oxidation of D-[U-14 C]fructose (3). A compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…For instance, it was shown that HK2 and HK4 are capable of phosphorylating fructose directly to F-6-P: Katzen et al determined the K m for glucose and fructose of rat HK2 to be 1.4×10 −4 M and 3.0×10 −3 M, respectively [29], and Malaisse et al reported that 25% of hepatic fructose in rats is phosphorylated to F-6-P by HK4 [30]. Studies have also shown that glucose confers kinetic cooperativity to human liver and β-cell hexokinase toward fructose phosphorylation to F-6-P [31], [32]. Finally, it is possible that active fructose metabolism to triose-phosphates could increase the intracellular G-6-P pool, and hence promote F-6-P generation and HBP flux through attenuation of glucose catabolism and not as a direct F-6-P precursor.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was shown that HK2 and HK4 are capable of phosphorylating fructose directly to F-6-P: Katzen et al determined the K m for glucose and fructose of rat HK2 to be 1.4×10 −4 M and 3.0×10 −3 M, respectively [29], and Malaisse et al reported that 25% of hepatic fructose in rats is phosphorylated to F-6-P by HK4 [30]. Studies have also shown that glucose confers kinetic cooperativity to human liver and β-cell hexokinase toward fructose phosphorylation to F-6-P [31], [32]. Finally, it is possible that active fructose metabolism to triose-phosphates could increase the intracellular G-6-P pool, and hence promote F-6-P generation and HBP flux through attenuation of glucose catabolism and not as a direct F-6-P precursor.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of metabolism, attention was drawn to the participation of different enzymes to the phosphorylation of the ketohexose, including fructokinase (1), the low-Km hexokinase (2), and the high-Km glucokinase with emphasis on the glucose-induced cooperativity of this enzyme towards D-fructose (3,4) and the anomeric specificity of such a process (5,6). The possible participation of D-fructose 1-phosphate in the regulation of glucokinase activity at the intervention of its regulatory protein (7) was also examined (Iwashiga K, et al, Diabetologia 38 (Suppl 1): abs.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many studies of the role of anomeric specificity in D-glucose metabolism in human pancreatic islets and other cell types have appeared which suggest that there is an anomer-specific glucose receptor present in the beta cells in humans. 3 Recently it was shown that the˛-anomer of 4 Similarly, other metabolic actions involving disaccharides, glyco-conjugates, and nucleosides may also be anomer specific. Consequently, precise determination of the anomeric configuration in solution is critical to a better understanding of the biological function and metabolism of mono/polysaccharides and carbohydrates.…”
Section: Introductionmentioning
confidence: 99%